Palindromes in Some Smarandache-Type Functions - Hary Gunarto; S.M.S. Islam; A.A.K. Majumdar (Jurnal Matematika MANTIK, 2022)
The objective of this paper is to investigate palindromes in three Smarandache-type arithmetic functions,namely, the Smarandache function S(n), the pseudo Smarandache function Z(n), and the Sandor-Smarandache function SS(n).